Design and development of an experimental rig to evaluate the performance of air-conditioner refrigerants - Ismail, Isma Nur Hafizi; Sabudin, Sulastri (Research Progress in Mechanical and Manufacturing Engineering, 2022)
R-22 is a hydrochlorofluorocarbon (HCFC) refrigerant commonly used in air-conditioner system but it have to be phase out by year 2020 because of its ozone depletion potential (ODP). Hydrocarbon (HC) refrigerant can be an alternative as a replacement, since they natural, non-toxic and compatible with lubricating oil. HC has nearly identical properties to R-22, gives the advantages to retrofit without having to replace any refrigeration system components. The objectives of this study are to design and develop an experimental rig due to air-conditioning, and to evaluate the performance of both R-22 and HC-22 refrigerants in split unit air-conditioner. The design process starts from sketching until developing virtual prototype model using Solidworks 2019 software. The manufacturing process to develop the rig also been proposed, including the process of measuring, cutting, drilling, welding, assembly, connecting and finishing. During the process, some modification has been done by changing the position of the outdoor unit in the opposite direction to the indoor unit and installing air duct around the outdoor unit to prevent hot air from approaching the indoor unit component. Overall, it can be concluded that the main objectives of this study were achieved. It is hope that the proposed design can be used in future learning and research purposes.